Out of business and on budget the challenge of military financing in Indonesia - Rieffel, Alexis, 1941- (United States-Indonesia Society : Brookings Institution Press, 2007)
"Describes the evolution of the military's business empire and its decline after 1998. Examines what is necessary to bring the Indonesian military "on-budget": what policies are required, what Indonesia can learn from other nations, and what a realistic timetable looks like"--Provided by publisher.